Examining students' self-set goals for self-regulated learning: Goal properties and patterns. Issue 11 (2nd November 2017) - McCardle, Lindsay; Webster, Elizabeth A.; Haffey, Adrianna; Hadwin, Allyson F.
Abstract : Task-specific goals play a critical role in self-regulated learning, yet little research has examined students' self-set goals for authentic study sessions. We propose high-quality goals that are useful for guiding task engagement and evaluating progress are specific about (a) time, (b) actions, (c) standards, and (d) content. In Study 1, we examined characteristics of students' self-set goals. Five categories were created to describe students' goals relative to the features of a high-quality goal. Students rarely included specific information regarding actions, standards, or content. In Study 2, we examined patterns of change in quality of self-set goals across a semester in which students were in a learning-to-learn course. Improvements in goal quality were either inconsistent or non-existent. Implications of vague goals for regulating learning are discussed.